Effects of Mind Mapping And Visual Imagery Instruction Strategies on Senior Secondary Schools Students' Scientific Attitude to Mechanics in Ekiti State of Nigeria - Ukoh, Edidiong E; ALADEJANA, Alaba Lawrence (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
The study examined the effects of visual imagery and mind mapping strategies on physics students' scientific attitude to mechanics in Ekiti state, Nigeria. The study adopted 3 X 1 pretest-posttest control group quasi experimental research design. Eight senior secondary schools were be purposively selected for the experimental groups, while four schools were purposively selected for the control group. This made a total of twelve schools that were selected from twelve local government areas across all the three senatorial districts of Ekiti state for the study. A total number of two hundred and forty six physics students from the selected schools were used. The instrument that the researcher used for the study was self-designed instruments titled: Students' Scientific Attitude to Mechanics. The data collected were analysed using descriptive statistics (mean, standard deviation) as well as inferential statistics such as Analysis of Covariate (ANCOVA) which was used to determine the significant mean and interaction effects to the variables of the study. Estimated Marginal Mean (EMM) was used to determine the performance of each group. Bonferroni pair wise and Scheffe Post-hoc analyses were also employed to trace the source of observed significance among the groups. The finding of the study revealed that there was significant effect of treatment on students' scientific attitude to mechanics. The result further showed that those exposed to visual imagery had the highest scientific attitude mean score, closely followed by those exposed to mind mapping while those taught with conventional method of teaching had the least. Also, the finding of the study showed that there was significant main effect of gender on students' scientific attitude to mechanics. Similarly, the finding showed that there was significant interaction effect of treatment and gender on students' scientific attitude. Based on these findings, it was therefore recommended that mind mapping and visual imagery instructional strategies should be used in improving students' scientific attitude.